Background information: Consider a European contingent claim with payoff $V(S_T)$, where $V: \mathbb{R}_+\rightarrow \mathbb{R}$ is a function which assigns a value to the payoff based on the price of the asset at terminal time $T$. Such European contingent claims are called Markovian claims. The claim is that the price $V_0$ of the European contingent claim $V(S_T)$ at time 0 is given by $$V_) = \frac{1}{(1+R)^T}\hat{\mathbb{E}}[V(S_T)]$$ provided that there is no arbitrage. Here $\hat{\mathbb{E}}$ is the expectation with respect to the (unique) risk neutral probability. As a free bonus we construct a replicating portfolio through a backward recursive scheme and show that at state $i$ at time $t$, the price $V_t^{i}$ of the European contingent claim is a function of the price of the underlying asset $S_t(i)$.

First notice that the price of the contingent claim at maturity time $T$ is equal $V(S_T(i))$ if the state $i$ occurs. Then, assume that the price of contingent claim $V_{t+1}^j$ is known at time $t+1$ for all states $j = 0,\ldots,t + 1 $ and is a function $V_{t+1}$ of $S_{t+1}(j)$, i.e. $V_{t+1}(S_{t+1}(j))$. Conditional on the state $i$ at time $t$, the state of the market at time $t+1$ is either $i+1$ or $i$. Therefore, we can use the result of the single period binomial tree to conclude that $$V_t^i = \frac{1}{1+R}(V_{t+1}^{i+1}\hat{\pi}_u + V_{t+1}^{i}\hat{\pi}_l) = \frac{1}{1+R}\hat{\mathbb{E}}[V_{t+1}|S_t = S_t(i)]$$ Here we used the fact the no arbitrage implies the existence of risk neutral probabilities with conditional probabilities $\hat{\pi}_u = \frac{1+R-l}{u-l}$ and $\hat{\pi}_l = \frac{u-1-R}{u-l}$ given state $i$ at time $t$. Notice that the above expression also suggests that $V_t^j$ is a function of $S_t(j)$, $$V_t(S);= \frac{1}{1+R}\hat{\mathbb{E}}[V_{t+1}|S_t = S] \ \ \ \ \ (1.6)$$ To replicate the payoff at time $t+1$, one needs to keep $$\frac{V_{t+1}^{i+1} - V_{t+1}^{i}}{S_{t+1}(i+1) - S_{t+1}(i)} = \frac{V_{t+1}(S_t(i)u) - V_{t+1}(S_t(i)l)}{S_t(i)(u-l)}$$ units of risky asset and $$\frac{uV_{t+1}^i - lV_{t+1}^{i+1}}{(u-l)(1+R)} = \frac{uV_{t+1}(S_t(i)l) - lV_{t+1}(S_t(i)l)}{(u-l)(1+R)}$$ risk free bonds in the replicating portfolio. In other words, the replicating portfolio is a self-financing portfolio by (1.1) with $w_0 = V_0$ and portfolio strategy given by $\Delta_0(S_0),\ldots,\Delta_{T-1}(S_{T-1})$ $$\Delta_t(S):= \frac{V_{t+1}(Su) - V_{t+1}(Sl)}{S(u-l)} \ \ \ \ \ \ (1.7)$$ The number of units of risky asset in replicating portfolio, given by (1.7), is called the Delta of the contingent claim at time $t$.

In the replicating portfolio for a European Markovian option with payoff $V(S_T)$, let $Y_t := S_T\Delta_t(S_t)$ be the amount of investment on the underlying asset. Then, use (1.6) and (1.7) to show $$Y_t = \frac{1}{1 + R}\hat{\mathbb{E}}[Y_{t+1}|S_t], \ \ \text{for} \ t = 0,\ldots, T-1$$

Attempted solution: Assume we have a replicating portfolio for a European Markovian option with pay off $V(S_T)$, let $$Y_t := S_t\Delta_t(S_t)$$ Now we know that $$\Delta_t(S_t) = \frac{V_{t+1}(S_tu) - V_{t+1}(S_tl)}{S_t(u-l)}$$ which represents the quantity of units of the risky asset we need to replicate. Also, we need $$\frac{uV_{t+1} - lV_{t+1}}{(u-l)(1+R)} = \frac{uV_{t+1}(S_tl) - lV_{t+1}(S_tl)}{(u-l)(1+R)}$$ risk free bonds in the replicating portfolio as well. These two quantities represent the replication of the pay off the investment defined by 1.6 in the book $$V_t(S) = \frac{1}{1+R}\hat{\mathbb{E}}[V_{t+1}|S_t = S]$$ Then given the fact the $Y_t = S_t\Delta_t$ then clearly $$Y_t = \frac{1}{1 + R}\hat{\mathbb{E}}[Y_{t+1}|S_t], \ \ \text{for} \ t = 0,\ldots, T-1$$

I am not sure if this is correct in any way,shape, or form. Any suggestions is greatly appreciated.


1 Answer 1


We show that \begin{align*} Y_t^i = \frac{1}{1+R}E\big( Y_{t+1} \mid S_t = S_t(i)\big).\tag{1} \end{align*} Note that \begin{align*} Y_{t+1} &= S_{t+1} \Delta_{t+1}(S_{t+1})\\ &=\frac{V_{t+2}(S_{t+1}u) - V_{t+2}(S_{t+1}l)}{u-l}. \end{align*} Then \begin{align*} \frac{1}{1+R}E\big( Y_{t+1} \mid S_t = S_t(i)\big) &= \frac{1}{1+R}E\left(\frac{V_{t+2}(S_{t+1}u) - V_{t+2}(S_{t+1}l)}{u-l} \mid S_t = S_t(i)\right)\\ &= \frac{1}{1+R}E\bigg(\pi_u\frac{V_{t+2}(S_{t+1}(i+1)u) - V_{t+2}(S_{t+1}(i+1)l)}{u-l}\\ &\qquad\qquad +\pi_l\frac{V_{t+2}(S_{t+1}(i)u) - V_{t+2}(S_{t+1}(i)l)}{u-l} \mid S_t = S_t(i)\bigg)\\ &= \frac{1}{1+R}E\bigg(\pi_u\frac{V_{t+2}(S_{t+2}(i+2)) - V_{t+2}(S_{t+2}(i+1))}{u-l}\\ &\qquad\qquad +\pi_l\frac{V_{t+2}(S_{t+2}(i+1)) - V_{t+2}(S_{t+2}(i))}{u-l} \mid S_t = S_t(i)\bigg)\\ &=E\left(\frac{V_{t+1}^{i+1}-V_{t+1}^{i}}{u-l}\mid S_t = S_t(i) \right)\\ &=E\left(Y_t^i\mid S_t = S_t(i) \right)\\ &=Y_t^i. \end{align*} The identity (1) is thus proved.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.